Changes in surface antigens of immature thymocytes under the influence of T-cell growth factor and thymic factors. - Chen, S S (1983)
Peanut agglutinin-positive thymocytes, peanut agglutinin-negative thymocytes, cortisone-resistant thymocytes, and unfractionated thymocytes were prepared from congeneic C57BL/6 Tla mice. By using surface iodination and immunoprecipitation of solubilized antigen with specific antisera (e.g., anti-H-2D, anti-TL, anti-Qa2/3, and anti-gp70), the released specific antigens were electrophoresed on polyacrylamide gels, and their radioactivity was measured. The relative percentages of surface antigens H-2D, TL, Qa2/3, and gp70 were 3.2%, 47.5%, 2.5%, and 46.8%, respectively, for peanut agglutinin-positive thymocytes; 31.8%, 4.4%, 32.7%, and 31.1%, respectively, for cortisone-resistant thymocytes; 13.2%, 28.7%, 12.3%, and 45.8%, respectively, for peanut agglutinin-negative thymocytes; and 7.7%, 27.1%, 4.3%, and 60.9%, respectively, for unfractionated thymocytes. After incubation with thymosin fraction V or T-cell growth factor (interleukin II) for 20 hr, the changes in surface antigens of peanut agglutinin-positive thymocytes closely correlated with their normal maturation (i.e., H-2D increases and TL decreases). Thymic factors (e.g., thymosin alpha 1, thymopoietin pentapeptide, facteur thymic serique) had only small or no effects on surface antigens of peanut agglutinin-positive thymocytes. The results suggest that peptides yet to be identified in thymosin fraction V may play an important role in intrathymic evolution and that T-cell growth factor is possibly a peripheral signal derived from activated T cells that modulates T-cell receptors and may be a critical regulator of intrathymic cellular development.